Persepsi Ibu terhadap Kepercayaan dan Pengalaman tentang Dukun Pijat Bayi di RT 13 Kelurahan X - Shinta Satriani; Dian Ardyanti; Emelia Tonapa (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Infant massage is a traditional touch therapy that has long been part of Indonesian culture, commonly performed by traditional birth attendants who are believed to possess skills based on experience and cultural values. Despite the growth of modern healthcare services, this practice is still used by some communities. This study aims to explore mothers’ perceptions regarding their trust and experiences in using the services of traditional infant massage practitioners in RT 13, Kelurahan X. The research employed a qualitative method with in-depth interviews involving mothers who had brought their babies to traditional infant massage practitioners. Data were analyzed thematically to identify patterns of perceptions and experiences. The findings show that traditional infant massage is still trusted and considered beneficial for infant health and comfort. Such trust is shaped by positive experiences, such as babies becoming calmer, sleeping better, and falling ill less frequently. Supporting factors include hereditary beliefs, personal experiences, family support, and social environmental influences. It can be concluded that the use of traditional infant massage services in RT 13, Kelurahan X is strongly influenced by culture, experience, and social support. It is recommended that mothers be more selective in choosing massage practitioners, healthcare providers deliver education and build collaboration with traditional practitioners, future research involve more participants with a participatory approach, and communities strike a balance between traditional beliefs and medical knowledge to ensure infant safety